Autonomia dos Países Bálticos: uma questão geopolítica - Rosevics, Larissa (2017)
The shores of the Baltic Sea are strategic areas disputed by centuries for the peoples of the region. The emancipation of Estonia, Latvia and Lithuania has always been threatened by the expansionism of Germany and Russia. This article seeks to demonstrate historically and geopolitically as Russian and German influence on the autonomy of the three Baltic States.